2020
DOI: 10.1155/2020/8580471
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Wavefront Autorefractors: Binocular Open-Field versus Monocular Closed-Field

Abstract: Purpose. To evaluate the agreement and repeatability between a new commercially available binocular open-field wavefront autorefractor, as part of the Eye Refract system, and a monocular closed-field wavefront autorefractor (VX110). Methods. A cross-sectional, randomized, and single-masked study was performed. Ninety-nine eyes of 99 healthy participants (37.22 ± 18.04 years, range 8 to 69 years) were randomly analyzed. Three measurements with the Eye Refract and the VX110 were taken on three different days, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…This interval is considerably large clinically and thus these instruments cannot be used interchangeably. Many of the previous studies have also shown similar large limits of agreement intervals [ 7 , 10 , 23 , 24 ]. The difference in the objective refraction values obtained with different autorefractometers are suggested to be caused by the fixation target, viewing conditions, fogging system, and wavefront sensors for measurements [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This interval is considerably large clinically and thus these instruments cannot be used interchangeably. Many of the previous studies have also shown similar large limits of agreement intervals [ 7 , 10 , 23 , 24 ]. The difference in the objective refraction values obtained with different autorefractometers are suggested to be caused by the fixation target, viewing conditions, fogging system, and wavefront sensors for measurements [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 67%
“…Our precision results showed good repeatability and reproducibility outcomes, and the limits never exceeded 0.70D for M and 0.40D for the cylindrical components. The autorefractometers available for clinical use have been shown to have good repeatability and reproducibility for measuring the objective refraction [ 7 , 14 , 18 , 19 , 20 ]. With the introduction of new instruments, the intra- and inter-session precision needs to be evaluated, although the objective refraction measurements are automated and are seldom influenced by the examiner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found similar values of repeatability for the sphere ( r = 1.96 D ; ICC = 0.983) compared to the Eye Refract in the keratoconus group (see Table 3 ). In healthy subjects, several studies measured objective refraction with different aberrometers, obtaining r values between 0.28 D and 0.59 D for the spherical equivalent [ 16 , 26 30 ]. These values were slightly better than the ones obtained with the Eye Refract in the healthy group (see Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and precision of the Eye Refract to estimate refractive errors has been confirmed in healthy subjects [ 14 , 16 ]. However, its repeatability to perform automated subjective refraction is still unknown in healthy subjects and other ocular conditions.…”
Section: Introductionmentioning
confidence: 99%